1990
DOI: 10.1164/ajrccm/141.6.1538
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Intrinsic Neurones and Possible Phenotypic Changes after Extrinsic Denervation of Human Respiratory Tract by Heart-Lung Transplantation

Abstract: Respiratory tract nerves have cell bodies outside (sensory, sympathetic) and inside (parasympathetic) the organ and contain bioactive peptides. These include calcitonin gene-related peptide and tachykinins (sensory nerves), vasoactive intestinal polypeptide (parasympathetic nerves), and neuropeptide with tyrosine (sympathetic nerves). Because transplantation interrupts the extrinsic nerve supply to the tissues, we have examined transplanted human respiratory tracts (n = 11) removed at retransplantation 2 to 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…The antisera used to detect SP and CGRP have both previously been substantiated in other tissue, be ing used to delineate neuropeptide-containing nerves in the central nervous system [ 16], skin [ 17] and respir atory tract [18]. Within resected lung tissue, SP-im munoreactive nerves are difficult to detect or absent, a finding consistent with the reported findings of Ol lerenshaw et al [11,12] in non-asthmatic subjects.…”
Section: Discussionsupporting
confidence: 69%
“…The antisera used to detect SP and CGRP have both previously been substantiated in other tissue, be ing used to delineate neuropeptide-containing nerves in the central nervous system [ 16], skin [ 17] and respir atory tract [18]. Within resected lung tissue, SP-im munoreactive nerves are difficult to detect or absent, a finding consistent with the reported findings of Ol lerenshaw et al [11,12] in non-asthmatic subjects.…”
Section: Discussionsupporting
confidence: 69%
“…The cause of this decline is unclear. Although not observed in all transplantation studies (Adeghate and Donath 1990; Korsgren et al 1992Korsgren et al , 1993Portis et al 1994;Shen et al 1993;Springall et al 1990), a similar decrease in the density of VIP-LI nerve fibers was also reported in rat ovaries autotransplanted to the neck (Lara et al 1992) and rat smooth muscle cells grafted to the anterior chamber of the eye (Hiebert and Smith 1994). It should be noted, however, that the AChE-positive innervation was not down-regulated in the present islet grafts.…”
Section: Discussionsupporting
confidence: 68%
“…In human airways, VIP-containing nerve fibers are dis tributed predominantly in tracheobronchial smooth mus cle, around blood vessels and seromucous glands and in nerve cell bodies of local ganglia [2,7,[27][28][29], NPY-containing fibers in human airways are localized mainly around blood vessels and within glands [2,11]. A few NPYcontaining nerve cell bodies have been demonstrated in local ganglia [2], SP-immunoreactive nerve fibers have been reported to be sparsely distributed in association with the epithelium, around blood vessels and glands and as single fibers within human airway smooth muscle [2,3,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%